Core clinical skills for OSCEs in medicine - Dornan, Tim (Elsevier/Churchill Livingstone, 2006)
This work comprises a set of medical tasks that are performed by every newly qualified doctor. The authors define the skills that must be acquired to perform them, then they are explained together with how they might measured.